Effectiveness of Digital Partographs on Clinical Decision-Making in the Delivery Process by Midwives - Widya Maya Ningrum (EMBRIO: Jurnal Kebidanan, 2023)
A partograph can be used as an early warning system that will help make early decisions when a mother should be referred, expedite or end monitoring of the fetus and mother during childbirth, as well as help find the presence of fetal or maternal problems. A digital partograph is a form of application where the use of digital paper instead of manual paper for monitoring is authentically designed by researchers. The use of partographs through devices that can be used as a tool to assist with medical care and facilitate it during tracking by the workforce can be downloaded from the Google Play Store. The purpose of this study is to analyze the use of Android-based digital partographs for clinical decision-making in the delivery process. The research method used in this study is a comparative study by looking at the differences between the two variables studied, namely the use of digital partographs with manuals for clinical decision-making in the delivery process with a crossectional approach. The results of data analysis using Man Whitney on the aspects of ease, speed, and relevance of the data obtained a p-value of less than 0.05 meaning that there is a significant difference between manual partographs and digital partographs from the aspects of ease, speed, and relevance of data to clinical decision making in the delivery process.